Metal‐Free Cyclization of ortho‐Nitroaryl Ynamides and Ynamines towards Spiropseudoindoxyls. Issue 20 (16th April 2018) - Marien, Niels; Reddy, B. Narendraprasad; De Vleeschouwer, Freija; Goderis, Steven; Van Hecke, Kristof; Verniest, Guido
Abstract: An efficient metal‐free cascade reaction between 1‐dibromovinyl‐2‐nitro‐substituted arenes and secondary amines results in the formation of polycyclic pseudoindoxyls in a single step. The reaction mechanism leading to these fused ring systems was investigated, and is believed to involve the initial formation of nitroarylated ynamines/ynamides. These intermediates cycloisomerize towards N‐alkenyl‐tethered 2‐aminoisatogens via a carbene intermediate as demonstrated by QTAIM (quantum theory of atoms in molecules) and ELF (electron localization function) analysis. A subsequent intramolecular dipolar cycloaddition afforded the title compounds. Abstract : Three in one : A metal‐free cascade reaction between ortho ‐nitroaryl dibromoalkenes and secondary amines generates spiropseudoindoxyls. These reactions proceed via an ortho ‐nitroaryl ynamine or ynamide, which is generated in situ and cycloisomerizes to afford three new rings in one step.